Management of anticoagulant therapy using a portable point-of-care international normalized ratio device and social networking service in a patient with a left ventricular assist device. Issue 4 (October 2020) - Asaka, Machiko; Nagatomo, Daisuke; Kotooka, Norihiko; Kaneko, Tetsuya; Yajima, Ayumu; Morooka, Toshifumi; Node, Koichi
Abstract: Device infection and stroke are still frequently reported as complications of left ventricular assist devices, and strict management of anticoagulation therapy is sometimes difficult at the time of infection status. We report the case of a 55-year-old man with a HeartMate II (Abbott, Inc., Abbott Park, IL, USA) as a bridge to cardiac transplantation. The patient measured his prothrombin time-international normalized ratio (PT-INR) by himself using a point-of-care device at home and reported the result promptly on a social networking service (SNS). Physicians instructed the patient on how to adjust his dose of warfarin based on the result and suggested the next time of measurement on the SNS. Until cardiac transplantation, we adjusted the dose of warfarin 106 times using the SNS because of unexpected PT-INR fluctuations caused by antibiotics. The time in the therapeutic range was maintained at 83.2% without complications, including major bleeding, stroke, or pump replacement; however, there was transient intra-pump thrombosis triggered by severe dehydration due to hyperthyroidism. <Learning objective: The strict control of the prothrombin time-international normalized ratio (PT-INR) is crucial to avoid complications in patients with left ventricular assist devices. However, this is sometimes difficult during infections. Although the self-measurement of PT-INR using a point-of-care device is recommended by the guideline, it is not clear who should adjust the dose of warfarin based on the results. A social networking service may help physicians to decide on the warfarin dose without delay, and this should complement monthly hospital visits.>